Adverse event profile of memantine and donepezil combination therapy: a real-world pharmacovigilance analysis based on FDA adverse event reporting system (FAERS) data from 2004 to 2023 - Yang, Yihan; Wei, Sheng; Tian, Huan; Cheng, Jing; Zhong, Yue; Zhong, Xiaoling; Huang, Dunbing; Jiang, Cai; Ke, Xiaohua (Frontiers in Pharmacology, 2024)
Real-world population data on the long-term safety of donepezil in combination with memantine are incomplete and variable. Therefore, the aim of this study was to analyze the adverse events (AEs) of donepezil in combination with memantine according to US Food and Drug Administration Adverse Event Reporting System (FAERS) data to provide evidence for the safety monitoring of this therapy. We retrospectively analyzed reports of AEs for the combination of donepezil and memantine from 2004 to 2023 extracted from the FAERS database. Whether there was a significant association between donepezil and memantine combination therapy and AEs was assessed using four disproportionality analysis methods. To further investigate potential safety issues, we also analyzed differences and similarities in the time of onset and incidence of AEs stratified by sex and differences and similarities in the incidence of AEs stratified by age. Of the 2400 adverse drug reaction (ADR) reports in which the combination of donepezil and memantine was the primary suspected drug, most of the affected patients were female (54.96%) and older than 65 years of age (79.08%). We identified 22 different system organ classes covering 100 AEs, including some common AEs such as dizziness and electrocardiogram PR prolongation; fall, pleurothotonus and myoclonus were AEs that were not listed on the drug label. Moreover, we obtained 88 reports of AEs in men and 100 reports of AEs in women; somnolence was a common AE in both men and women and was more common in women, whereas pleurothotonus was a more common AE in men. The three age groups had distinctive AEs, but lethargy was the common AE among all age groups. Finally, the median time to AE onset was 19 days in all cases. In both men and women, most AEs occurred within a month of starting donepezil plus memantine, but some continued after a year of treatment. Our findings may provide valuable insights for further studies on the safety of donepezil and memantine combination therapy, which are expected to contribute to the safe use of this therapy in clinical practice.